2013
DOI: 10.1093/heapro/dat073
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion in Swedish schools: school managers' views

Abstract: Schools are recognized worldwide as settings for health promotion, and leadership has a bearing on schools' ability to be health promoting. School managers have a great influence on what is prioritized in school, which in turn affects students' school performance and health. There is lack of research into school managers' views on health promotion, and what they consider to be central to health promotion. The aim was therefore to examine school managers' views about what health promotion in schools include. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
1
9
0
4
Order By: Relevance
“…This calls for a holistic educational environment, where health promotion, health literacy, and focus on equity between students and teachers are aligned [4,5,6]. The findings revealed by this study consistently centre around the health-promoting factors of collaboration and participation, which fits with the whole-school approach [12]. Add that collaboration between stakeholders (i.e., students, teachers, parents, communities, researchers) is often challenging because their values, cultures, and traditions differ [10].…”
Section: Collaboration Among School Staffsupporting
confidence: 56%
“…This calls for a holistic educational environment, where health promotion, health literacy, and focus on equity between students and teachers are aligned [4,5,6]. The findings revealed by this study consistently centre around the health-promoting factors of collaboration and participation, which fits with the whole-school approach [12]. Add that collaboration between stakeholders (i.e., students, teachers, parents, communities, researchers) is often challenging because their values, cultures, and traditions differ [10].…”
Section: Collaboration Among School Staffsupporting
confidence: 56%
“…After analyzing the curricula discussed above, we highlight the need to include EpS in official degrees, an issue that is also evident in several recent studies at national 48 and international [52][53][54] levels.…”
Section: Curricular Restructuringmentioning
confidence: 99%
“…In school, the classroom is where children spend most of their time, and a beneficial classroom climate is of substantial importance in establishing a supportive and healthy school environment (WHO 1991 ; Persson and Haraldsson 2013 ). It has been shown that an important aspect of the classroom climate is children’s own perception of it (Gillen et al 2011 ; Hagquist 2012 ; Veerman 2015 ).…”
Section: Introductionmentioning
confidence: 99%